PERLINDUNGAN HUKUM BAGI PIHAK KREDITUR APABILA TERJADI WANPRESTASI YANG DILAKUKAN OLEH DEBITUR - Tangkas Eka Putra; Hanafi Tanawijaya (Jurnal Hukum Adigama, 2021)
Before the creditor submits an execution auction request to the KPKNL, the creditor submits amicable steps to the defaulting debtor to pay off his debt immediately, if there is no good faith from the defaulting debtor to pay off his debts, the bank submit a mortgage execution auction to the KPKNL. After fulfilling the conditions stipulated in Article 11 of the Regulation of the Minister of Finance of the Republic of Indonesia Number. 27/PMK.06/2016 concerning Auction Implementation Guidelines, and if all are stated as complete and formally correct, the seller can determine the bidding method by including in the auction announcement and the place where the auction is held is in the position of the class II auction official where the goods are located. The timing of the auction is determined by the head of the KPKNL or a class II official. Legal protection for creditors is contained in Law Number 4 of 1996 concerning Mortgage Rights on Land and objects related to land. Lawsuits and opposition to the auction of mortgage executions, in principle, do not delay the execution of mortgages, but in fact have a juridical and legal impact. With a large economy, the purpose of the lawsuit against the auction is solely aimed at making it difficult for the Mortgage Holder to settle his receivables quickly. The lawsuit and opposition to the mortgage execution auction in principle does not delay the execution of the mortgage right, but it has a large juridical and economic impact. According to the author, the purpose of the lawsuit against the auction is solely aimed at making it difficult for the mortgage holder to settle his receivables quickly, and harming the auction buyer who has good intentions in controlling the mortgage object that has been purchased in a public auction.